Creative Strategy in Advertising / Seventh Edition - Drewniany L. Bonnie; Jewler Jerome A (Belmont, CA Wadsworth - Thomson Learning, 2001)
This book prepares you to plan and execute effective campaigns in today's complex markets. Preface, Creating Unexpected but Relevant Selling Messages, Targeting a Diverse Marketplace, Strategy: The Creative Before the Creative, Finding the Big Idea, Working in Print, Designing to Communicate, Working in Television, The Internet: The Ultimate Direct, Retail Advertising, Convincing the Client, Now It's Time to Land that Job, Index.